Relationship between Mindfulness and Interest in Learning among Cognition of SMK Metta Maitreya Pekanbaru Students - Handomo Lesmana (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2022)
The study used stratified random sampling of 131 students from 195 SMK students. The research design was a quantitative correlational approach, associative hypothesis, and cross-sectional survey method. The instrument for collecting data was a closed questionnaire via Google Forms. The questionnaire results were tested through instrument testing of validity and reliability, classical assumptions, correlation analysis, and simple and multiple regression with a level of = 0.05. The results of data analysis: (1) There is a low, positive, significant relationship between mindfulness and cognition, the correlation value is 0.271, the coefficient of determination is 0.073, and the effective contribution is 5.420%; (2) There is a low, positive, significant relationship between interest in learning and cognition, the correlation value is 0.270, the coefficient of determination is 0.073, and the effective contribution is 5.346%; (3) There is a low, positive, significant relationship between mindfulness and interest in learning simultaneously with cognition, the correlation value is 0.328, the coefficient of determination is 0.108, and the total effective contribution is 10.766%. The study's results conclude that students' cognition can be improved through increased mindfulness and student interest in learning, either partially or simultaneously.